Theileriosis in naturally infected roan antelope (Hippotragus equinus). Issue 6 (November 2022) - Clift, Sarah J.; Martí-Garcia, Bernat; Lawrence, John A.; Mitchell, Emily P.; Fehrsen, Jeanni; Martínez, Jorge; Williams, June H.; Steyl, Johan C. A.
Cases of Theileria -associated mortality are rarely reported in African wild artiodactyls. Descriptions of lesions are limited, particularly in endangered hippotraginids. Here, we analyzed retrospectively the gross and histologic findings in 55 roan antelope ( Hippotragus equinus ) with fatal natural theileriosis. The most frequently recorded gross findings in 40 cases were widespread petechiae and ecchymoses (72.5%), probable anemia (67.5%), icterus (60%), splenomegaly (60%), hepatomegaly (52.5%), and pulmonary edema (50%). Histologic lesions in 34 cases were characterized by multi-organ infiltrates of parasitized and nonparasitized mononuclear leukocytes (MLs), and fewer multinucleate giant cells (MNGCs). Liver, lung, kidney, adrenal gland, and heart were most consistently infiltrated, followed by spleen and lymph nodes. Leukocytes were phenotyped in lung, liver, kidney, and heart specimens from 16 cases, using immunohistochemistry to detect CD20, CD3, myeloid/histiocyte antigen (MAC387), IBA-1, and CD204 surface receptors. A roan polyclonal anti- Theileria sp. (sable) antibody was applied to the same tissues to identify intraleukocytic parasite antigens. Similar proportions of intravascular and extravascular IBA-1-, CD204-, and MAC387-reactive putative monocyte-macrophages and fewer CD3-positive putative T-lymphocytes were identified in all organs, especially the lungs in infected roan. CD20-positive putative B-lymphocytes were significantly scarcer than in uninfected controls. Intraleukocytic Theileria parasites labeled consistently in affected tissues. Some parasitized and nonparasitized MLs and the MNGCs failed to label with selected leukocyte markers. Fatal theileriosis in roans may largely be the result of multi-organ monocyte-macrophage activation with associated tissue injury and overwhelming systemic inflammation. The identity of the parasitized leukocytes and characteristics of the lymphohistiocytic response require further clarification in roans.